Mental and social wellbeing trajectory during the pandemic for vulnerable populations - Andrew Joyce; Andrew Joyce; Thach Tran; Ruby Stocker; Jane Fisher (Frontiers Media S.A., 2024)
ObjectivesWe investigated changes over time in mental and social wellbeing indicators for vulnerable population subgroups during the pandemic. These groups were younger people, people with disabilities, low-income groups, unemployed, culturally, and linguistically diverse communities (CaLD), and Aboriginal and Torres Strait Islander peoples.MethodsA series of four repeated population representative surveys were conducted in June 2020, September 2020, January 2022, and June 2022. Questions included items on psychological distress, financial hardship, social connection, and life satisfaction.ResultsFor most groups, social connection and life satisfaction improved in 2022 relative to 2020. Psychological distress and financial hardship showed the opposite pattern, with some groups having worse results in 2022 relative to 2020. People without any vulnerability had better mental health and social wellbeing outcomes at each time point relative to the vulnerable population subgroups.ConclusionPandemic-related policies had differential effects over time and for different population groups. Future policies and research need to closely monitor how they impact population subgroups, and the overall results clearly demonstrate the inequity in mental health and social wellbeing outcomes for vulnerable population cohorts.